Proline Accumulation and Growth of Bean Leaf (Phaseolus vulgaris L.) With Biochar Application in The Shallow Water Table Environment - Meihana, Mei; Lakitan, Benyamin; Harun, M. Umar; Susilawati, Susilawati; Siaga, Erna; Widuri, Laily Ilman; Kartika, Kartika (Department of Agronomy and Horticulture, IPB University, 2023)
Agronomic constraints for vegetable cultivation in riparian wetlands are low soil quality and shallow water table conditions. This study aims to identify the effect of biochar application and shallow water table on proline accumulation and plant growth of bean leaf (Phaseolus vulgaris L.) at the generative stage. This study was carried out from April to August 2018 in factorial randomized block design. The first factor was doses of biochar (0, 1, and 2 kg.m-2), and the second was shallow water table condition (20 cm and 10 cm below the soil surface) given in the generative stage. The results showed that biochar application and the shallow water table significantly affected leaf parameters; proline accumulation and increases in the sucrose levels occurred on the leaves. Proline content increased started at 3 days after treatment (DAT) and decreased at 6 DAT until recovery day (7 DAT). The biochar application of 2 kg.m-2 provided good aeration in the soil, which enhanced the bean's ability to survive under excess water. Proline accumulation is one of the adaptation mechanisms of beans to abiotic stress in shallow water table conditions.